Zoomorphic : new animal architecture - Aldersey-williams, Hugh. (London : Collins Design, 2003)
A quirky trend of building designs inspired by bizarre animals has emerged in the last few years. Why and how has this happened? Is it because of new technical possibilities in materials and structural engineering? Or is the answer to be found in new social preoccupations in science? After a brief look at the historical precedents, the book focuses on contemporary examples from around the world and shows the various ways in which the organic/animal forms inform the architectural ones. Featured architects include Frank Gehry, Michael Sorkin, and Greg Lynn.